Meningkatkan Hasil Belajar Tema 4 Subtema1 Dengan Media Audio Visual Kelas II SDN 1 Selopuro - Wardayu, Arini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to determine whether using Audio Visual media can improve student learning outcomes in grade 2 SD Negeri 1 Selopuro. The problem studied in this research is how much improvement in learning outcomes with audio-visual media in Class 2 SD Negeri 1 Selopuro? The research uses Classroom Action Research, namely by research in the form of collaboration or collaboration between researchers with teachers and students. The results showed that learning theme 4 with audio visual media in grade 2 students of SDN 1 Selopuro improved better, student activity in learning and sending LKPD assignments on time. Negeri 1 Selopuro, it can be seen where in the pre-cycle the average value of student learning outcomes is 68, 33 with class completeness reaching 50% to 95 during the first cycle with 100% class completeness.